The Nigerian Budgeting Process A Framework for Increasing Employment Performance - Faleti, Kazeem Olabode; Myrick, Darrell (Mediterranean Journal of Social Sciences, 2012)
There have been several systematic inquiries into the functioning of Nigeria’s budgetimplementation process, and employment performance, particularly over the past fewdecades in order to diagnose the country’s budget implementation problems. This articlereports on an investigation into the effects of the formal budgeting process, budgetaryparticipation, sector size, and ownership on the employment performance of Nigerianministries, departments, agencies and parastatals. The study drew on observations from thearea of financial planning and control and its influence on employment performance, andwas conducted to fill the gap in previous literature about how budgeting practice affectsemployment performance. Hopefully, this theoretical exploration will provide fresh insightinto the possible correlation between budgeting practice and employment performance. Acombination of financial and non-financial measurements is suggested to reflect theeffectiveness of budgeting practice on employment performance. The findings provide moreevidence regarding the impact of the budgeting process on employment performance, andsuggestions for increasing employment performance level in Nigeria are provided, thusproviding possible solutions to similar challenges faced by other developing countries.